Evolution of a thermal mixing layer in uniformly sheared turbulent flow. - Ferchichi, Mohsen. (University of Ottawa (Canada), 1991)
Turbulent mixing and transport are very important phenomena due to their relevance in diverse applications (e.g. turbulent mixers, contamination of oceans and the atmosphere). For a better understanding of these phenomena, an experiment dealing with the development of a thermal mixing layer in uniformly sheared turbulent flow has been conducted. This experiment consists of introducing a stepwise increase in the mean temperature to the flow by electrically heating a set of thin ribbons, spanning half of a wind-tunnel cross-section. Hot wire anemometery and cold wire thermometry were used to measure the means and fluctuations of velocity and temperature. The downstream growth of the thermal mixing layer and the distributions of r.m.s. temperature fluctuations, thermal fluxes and other scalar field statistics are reported. Measurements show that the thermal field reaches a quasi-asymptotic state and that the thermal mixing layer penetrated deeper into the low speed side than into the high speed side of the flow. The study also includes theoretical attempts to predict the layer's growth.
Keywords: Engineering, Mechanical.